Dodonaea viscosa Jacq. induces cytotoxicity, antiproliferative activity, and cell death in colorectal cancer cells via regulation of caspase 3 and p53 - Herrera-Calderon, Oscar; Herrera-Ramírez, Angie; Cardona-G, Wilson; Melgar-Merino, Elizabeth Julia; Chávez, Haydee; Pari-Olarte, Josefa Bertha; Loyola-Gonzales, Eddie; Kong-Chirinos, José Francisco; Almeida-Galindo, José Santiago; Peña-Rojas, Gilmar; Andía-Ayme, Vidalina (Frontiers in Pharmacology, 2023)
Colorectal cancer (CRC) is the third most common cancer diagnosed worldwide and is the second leading cause of cancer-related death due to an insufficiency prognosis and is generally diagnosed in the last step of development. The Peruvian flora has a wide variety of medicinal plants with therapeutic potential in several diseases. Dodonaea viscosa Jacq. is a plant used to treat inflammatory process as well as gastrointestinal diseases. The aim of this study was to examine the cytotoxic, antiproliferative, and cell death-inducing effects of D. viscosa on colorectal cancer cells (SW480 and SW620). The hydroethanolic extract was obtained by maceration at 70% ethanol, the phytochemical constituents were identified by LC-ESI-MS. D. viscosa revealed 57 compounds some of them are: isorhamnetin, kaempferol, quercetin, methyl dodovisate B, hardwickiic acid, viscosol, and dodonic acid. Regarding the antitumoral activity, D. viscosa induced cytotoxic and antiproliferative activity in both SW480 and SW620 cancer cells, accompanied with, important changes in mitochondrial membrane potential, formation of the Sub G0/G1 population and increasing levels of apoptotic biomarkers (caspase 3 and the tumor suppressor protein p53) in the metastatic derivative cell line (SW620), suggesting an intrinsic apoptotic process after the treatment with the hydroethanolic extract of D. viscosa.